A proposal for the design of r&d indicators in higher education spaces - Rossi, Silvano (2022)
This study presents the design of a set of R&D indicators specifically related to applications and grants for beginners in scientific & technological activities in a higher education institution. Initially, we propose the construction of a scorecard with a set of indicators and goals for the strategic aim of increasing the number of students with the mentioned scholarships. The general objective is their future integration into the institution's balanced scorecard. This paper explains the methodology for implementing the indicators, the scorecard, and the analysis of the measurements provided by the indicators for the subsequent decision-making and necessary actions.  We conclude that the implemented scorecard offers the information required for management through indicators.